“D.I.Y. Boiler in Thung Bo Paen Style” Innovative Energy Management Model by Process Innovation - Yongprayun, Rawipha; Wongchai, Warakhom; Punin, Weera (Area Based Development Research Journal, 2019)
This research aims to 1) evaluate the efficiency of “D.I.Y. Boiler in Thung Bo Paen Style” in comparison with an old-styled steel energy-saving furnace for mushrooms steaming in Ban Thung Bo Paen Community Enterprise Group, Hang Chat district, Lampang province; 2)to disseminate the community wisdom by Participatory Action Research (PAR) process. The process include sharing the innovative design, collecting actual data and adjusting the mechanism of the old-styled steam stove to fit the newly invented the “D.I.Y. Boiler in Thung Bo Paen Style”. The results indicate that the mechanism of steam production against the average efficiency value of the “D.I.Y. Boiler in Thung Bo Paen Style” counts for 8.80% and is equivalent to that in a double pass boiler which is the same type of low-pressure steam stove in the provincial energy project. The replacement of the original stove, a 200-liter tank-style stove, with the “D.I.Y. Boiler in Thung Bo Paen Style”, raises the income by saving firewood cost of 2,910 baht per person per time, or approximately 3 baht per mushroom cube. Considering the overview if members steam the mushroom material three times per month on average, within a year they will earn an additional income of 104,760 baht per person. Also, when applying “D.I.Y. Boiler in Thung Bo Paen Style”, the greenhouse gas emissions are calculated to be reduced by 8,307.68 kgCO2 per person per year. Thus, a total of 10 members will reduce greenhouse gas emissions by 83 tonCO2 per year. Last but not least, the community has proposed to form "Sala" group, consisting of community technicians for maintenance and advice in case of problem with the use of “D.I.Y. Boiler in Thung Bo Paen Style”. The group will promote product sustainability and knowledge dissemination to those interested or nearby communities.